Evidence from NHANES 2011–2014: a correlation between the weight-adjusted-waist index and cognitive abilities in the United States - Zhao, Chan; Xu, Xintian; Hao, Chunyan (Frontiers in Aging Neuroscience, 2025)
BackgroundObesity exerts a significant detrimental impact on cognitive function. The weight-adjusted waist index (WWI) serves as a more precise indicator of visceral obesity that is independent of weight, in contrast to body mass index (BMI). Still, little research has been conducted on the interrelation between WWI and cognitive abilities. This investigation explored the link between WWI and older Americans’ cognitive function.MethodsUtilizing data from the 2011–2014 National Health and Nutrition Examination Cross-Sectional Survey, multiple linear regression analysis was used to assess the influence of WWI on cognitive abilities in those over 60. Three cognitive assessments were administered: the Animal Fluency Test (AFT), the Digit Symbol Substitution Test (DSST), and the Word Learning and Recall Module from the Coalition to Establish a Registry for Alzheimer’s Disease (CERAD). We implemented threshold effects analysis and smoothed curve fitting to elucidate the nonlinear relationship. Additionally, we analyzed subgroups to check for variability.ResultsThere were 2,762 participants, including1,504 (54.45%) females and 1,258 (45.55%) males. 53.77% of them had completed high school or above, and their average age was 69.05 ± 6.62. After controlling for confounding variables, the improved model predicted a negative connection between WWI and CERAD-Total, AFT, and DSST scores (all p < 0.05). Furthermore, we performed a smoothenable curve fitting between WWI and cognitive function scores, resulting in a nonlinear connection and a threshold saturation effect. We also executed subgroup analyses and interaction tests based on gender, race, educational background, marital status, diabetes, body mass index, alcohol consumption, hypertension, smoking habits, stroke, depression, and sleep quality to assess whether the relationship between WWI and cognitive function was affected by heterogeneity across different population segments. The subgroup analysis found no significant differences in cognitive performance associated with WWI across the various subgroups.ConclusionHigher WWI levels are associated with impaired cognitive function in Americans aged 60 and older.